Experimental Study on the Gasification Characteristics of Biomass with CO2/Air in an Entrained-flow Gasifier - Haimiao Yu; Geng Chen; Yangyang Xu; Dezhen Chen (BioResources, 2016)
This study explored the gasification characteristics of pine sawdust and rice straw with CO2/air in a bench-scale entrained-flow gasifier. The effects of various gasification parameters, i.e., CO2/C, temperature, and biomass type, on the syngas composition, gasification index, and tar yield were investigated. When compared to air gasification, the CO2/air agent for gasification improved the yield of CO, and it decreased the tar yield and the yield of CO2 produced from biomass. The cold gas efficiency (CGE) of pine sawdust reached 87.06% at the CO2/C equivalence ratio of 0.25, whereas that of rice straw reached 73.35% at the CO2/C equivalence ratio of 0.50. When compared with air gasification, the CO2/air gasification increased the CGE of pine sawdust and rice straw by 4.20% and 9.17%, respectively. However, excessive CO2 was unfavorable to the gasification process. As the temperature increased, the yields of CO and H2 increased, and the tar yield decreased, thus improving the syngas quality. This study indicated that the addition of the proper level of CO2 for gasification improved the overall gasification efficiency. Moreover, the improvement for rice straw (herbaceous plant) was more noteworthy than for pine sawdust (woody plant).